Coordinated Capacity Reductions and Public Communication in the Airline Industry - Gaurab Aryal; Federico Ciliberto; Benjamin T. Leyden (Center for Economic Studies and ifo Institute (CESifo), 2020)
We investigate whether legacy U.S. airlines communicated via earnings calls to coordinate with other legacy airlines in offering fewer seats on competitive routes. To this end, we first use text analytics to build a novel dataset on communication among airlines about their capacity choices. Estimates from our preferred specification show that when all legacy airlines in a market discuss the concept of "capacity discipline," they reduce offered seats by 1.79%. We verify that this reduction materializes only when airlines communicate concurrently, and that it cannot be explained by other possibilities, including that airlines are simply announcing to investors their unilateral intentions to reduce capacity, and then following through on those announcements. Additional results from conditional-exogeneity tests and control function estimates confirm our interpretation.
Keywords: D22; L13; L41; L93; 330; airlines; communication; capacity discipline; text data